Temi e principi della dottrina mariana di Sant’Agostino d’Ippona - Charamsa, Krzysztof (Alpha omega, 2012)
Inspired by a keen interest in modern theology for the resumption of Augustinian Mariology, of which important traces are found in the Mariology of Vatican II (Lumen Gentium, 52-69), the article presents in a systematic way the main issues and guidelines of the Marian theology of the bishop of Hippo. In the light of the Christ-centeredness of Augustinian Mariology twelve doctrinal themes and principles covered by the theologian are enucleated: Mary's cooperation in redemption, the divine motherhood, spiritual motherhood for believers, virginity, the issue of the vow and the marriage with Joseph, the role of exemplar for married couples and for consecrated persons, the Marian sign of assurance for the anthropological dignity of both sexes in relation to salvation, freedom from sin, the conditions for a devotion to Mary, Mary as the noblest new earth in the midst of the whole universe. Not neglecting further important developments in Mariology, in Augustine we found already the essentials of the Catholic Marian corpus, and we can see an openness to several Marian themes that will be specified only later.